Local acceptance of mineral exploration and exploitation activities : analysis of Finnish mineral policy in the period of 2019-2022 - Iriart, María Sol (2023)
This study analyzes how local acceptance of mineral exploration and exploitation activities was addressed in Finnish mineral policy between 2019-2022, following the Sanna Marin Government Programme's aim of improving local acceptability and opportunities for citizen influence in the development of mining projects. This period was marked by the reform of the Mining Law of 2011. This research explores the theme from the perspectives of land use planning, public participation, access to information and impacts on other sectors/activities. It analyzes a core set of themes identified to be relevant when discussing acceptance of mineral exploration and mining and the building of higher levels of social license to operate (SLO). This study joins in the discussions that revolve around the relationship or interplay between public policy and the social acceptance of mineral exploration and mining, being this framed in contemporary debates on mining governance and sustainable development. This study uses the concept of social license to operate (SLO), emphasizing the terms of acceptance and legitimacy, to frame and guide, in part, the present research. Complementarily, the concept of sustainable development is introduced for the analysis of the various subjects and aspects explored. This thesis analyzes official policy documents from the Government of Finland. The qualitative documental-based content analysis is complemented by different academic sources and contrasted with existing studies on the themes tackled. Findings showed that reforms mainly stress the municipal land use plans and strengthen the coordination of different interests locally when mineral exploration and exploitation activities are planned and promote greater protection and safeguarding of local business activities and livelihoods. Municipal decision-making power in land use planning is strengthened when considering future mining activities. Citizens' participation and access to information are reinforced by stipulating new public participation opportunities while developing exploration or exploitation activities. The permit process is strengthened with more information sessions for citizens and notification obligations reaching both planned and ongoing projects and targeting both the mining authority and the operator. More notifications in the reservation, prospecting and exploration phases are introduced, seeking to reinforce early access to information by relevant local stakeholders. This study suggests that some of the subjects and aspects covered in the draft of the Mining Act are introduced in a general manner, leaving some room for interpretation—this can pertain to the substance of the matter and the procedure to follow. It also suggests that to complement the proposed changes, policy documents such as plans, programmes, or guides could be used to delve into some aspects of the reforms and eventually bring more clarity to potential stakeholders. If well implemented, these reforms may offer more safeguards to local stakeholders from the early stages of mining projects.